PENYULUHAN PENGGUNAAN PETA DESA MENGGUNAKAN UNMANNED AERIAL VEHICLE (UAV) DI KECAMATAN CIMENYAN, KABUPATEN BANDUNG - Lumban Raja, Denny; Rikmayanthi Kirana, Fidela; Finlandini, Nadya; Rahman, Muhammad; Avrio Simatupang, Christopher; Aditya, Reinaldy (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Creating a village map is essential for regional development planning. However, it can be costly and time-consuming. The purpose of community service is to map the area around Mandalamekar Village, Cimenyan District, Bandung Regency, as one of the supporting documents for village planning based on disaster mitigation. The scope of this community service activity includes field data acquisition, such as creating flight paths and aerial photography using UAV vehicles, as well as data processing, including ortho mosaic, digitizing maps, and spatial analysis. The community service activity will produce an Aerial Photo Image Map and Land Use Map of Mandalamekar Village, both of which will be created at a scale of 1:5000. The output from the Community Service activity can be utilized for village development planning based on disaster mitigation. Furthermore, training on drone operation and processing has been conducted with the expectation that employees of Mandala Mekar Village can utilize drone technology. The feedback from the survey suggests that the Community Service activity is aligned with the users' requirements and has the potential to offer solutions for Mandala Mekar Village.